Body weight and risk of myocardial infarction and death in the adult population of eastern Finland. Issue 6599 (12th September 1987) - Tuomilehto, J; Salonen, J T; Marti, B; Jalkanen, L; Puska, P; Nissinen, A; Wolf, E
Abstract : Body mass index (weight (kg) divided by height squared (m2] and its association with the risk of myocardial infarction and death from all causes were studied prospectively in a randomly selected population sample in eastern Finland aged 30-59 at outset in 1972. The study population consisted of 3786 men and 4120 women. The participation rate in the survey in 1972 was over 90%. All deaths and admissions to hospital in the sample were obtained from the National Death Certificate and Hospital Discharge Registers. During the seven years of follow up until 1978, 170 men and 52 women had acute myocardial infarction, and during the nine years up to 1980, 223 men and 92 women died. Independent of age, men with a body mass index of 28.5 or more had a significantly higher incidence of acute myocardial infarction. This effect was also independent of smoking but not independent of biological coronary risk factors--that is, serum cholesterol concentration and blood pressure. In the analysis stratified for smoking in men the body mass index total mortality curve was J shaped among non-smokers, whereas smoking entirely outweighed body mass index as a predictor of death. Body mass index did not contribute significantly to the risk of either acute myocardial infarction or death in women. It is concluded that a body mass index of around 29.0-31.0 or more is not only a marker for coronary risk factors but is also a predictor of acute myocardial infarction in men.